2014
DOI: 10.1002/ccr3.185
|View full text |Cite
|
Sign up to set email alerts
|

Primary rectal diffuse large B‐cell lymphoma associated with ulcerative colitis: a case report

Abstract: Key Clinical MessageWe need to be aware of primary intestinal lymphoproliferative disease (PILD) associated with ulcerative colitis (UC). We should carefully monitor UC patients, particularly patients who meet the following conditions; a previous Epstein-Barr virus infection, treatment duration ≧4 years, male, and age ≧50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, the incidence rate of perforations in gastrointestinal lymphoma is approximately 9–22% and is higher than that in high-grade lymphoma (i.e., DLBCL) [ 2 – 4 ]. Primary gastrointestinal lymphoma may decrease the mechanical strength of the gastrointestinal wall and cause intestinal perforation [ 3 , 15 ]. Some studies have found that perforation is a poor prognostic factor in patients with high-grade lymphomas like DLBCL [ 2 – 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence rate of perforations in gastrointestinal lymphoma is approximately 9–22% and is higher than that in high-grade lymphoma (i.e., DLBCL) [ 2 – 4 ]. Primary gastrointestinal lymphoma may decrease the mechanical strength of the gastrointestinal wall and cause intestinal perforation [ 3 , 15 ]. Some studies have found that perforation is a poor prognostic factor in patients with high-grade lymphomas like DLBCL [ 2 – 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the clinicopathological data of 11 cases of DLBCL complicating UC published in the English literature, including our case, as shown in Table 1 [1,[3][4][5][6][7][8][9][10][11]. The age at diagnosis ranged from 20 to 73 (median, 55) years.…”
Section: Discussionmentioning
confidence: 99%
“…According to data found in PubMed between 2001 and 2019, only ten cases of diffuse large B-cell lymphoma (DLBCL) complicating UC, including one case of large B-cell lymphoma with unknown details, have been reported [1,[3][4][5][6][7][8][9][10][11]. Approximately half of these cases are closely related to the long-term usage of immunosuppressants (70%, 7/10 cases) and a very high rate of Epstein-Barr virus (EBV) infection (80%, 4/5 cases) and are classified as Oii-LPD.…”
Section: Introductionmentioning
confidence: 99%
“…Although overall similarities were apparent between the 2 cases with respect to the clinical spectrum of the diseases, notable differences included the presence of both EBV-positive lymphocytes and previous exposure to immunomodulatory agents in the reported case. 10 This suggests that perhaps there are other underlying mechanisms that predispose the UC patient to NHL. One theory is that chronic colorectal inflammation leads to overstimulation of the immune system and proliferation of immune cells.…”
Section: Discussionmentioning
confidence: 99%